Understanding Quality of Life in Brunei Darussalam - Blessing Gweshengwe; Noor Hasharina Hassan; Hairuni Mohamed Ali Maricar (Cogent Social Sciences, 2020)
Brunei Darussalam (hereafter Brunei) aspires to be one of the countries in the world with the highest Quality of Life by 2035. However, there is a dearth of studies on the meaning of Quality of Life and characteristics of a high Quality of Life in Brunei. This study examined the conceptualisation of Quality of Life by the Government of Brunei and descriptions of a high Quality of Life within the country. It also analysed the constructs that inform such a conceptualisation and such descriptions. Lastly, the study assessed the conceptualisation of Quality of Life in Brunei using the principles for conceptualising Quality of Life. It employed a mixed methods approach and drew data from government policy documents and interviews with 208 purposively selected households. The study found that the government construes Quality of Life, through the capability lens, as having a population that is well-educated, highly skilled and healthy, among other elements; lives harmoniously and peacefully; and engages effectively in economic and social activities. Descriptions of a high Quality of Life in Brunei, expressed through the basic needs and capability lenses, include “fulfilled basic needs”, “being financially secure”, ‘being well-educated”, “having a well-paying and permanent job”, “living comfortably” and “being healthy”. These descriptions are, by and large, similar in urban and rural areas. Moreover, the descriptions are similar to those held in other Southeast Asian countries. The conceptualisation of Quality of Life in Brunei is sound in that it satisfies Quality of Life conceptualisation principles.